Characterization of antibody and memory T-cell response in H7N9 survivors: a cross-sectional analysis. (February 2020) - Ma, M.-J.; Wang, X.-X.; Wu, M.-N.; Wang, X.-J.; Bao, C.-J.; Zhang, H.-J.; Yang, Y.; Xu, K.; Wang, G.-L.; Zhao, M.; Cheng, W.; Chen, W.-J.; et al.
Abstract: Objectives: Despite the importance of immunological memory for protective immunity against viral infection, whether H7N9-specific antibodies and memory T-cell responses remain detectable years after the original infection is unknown. Methods: A cross-sectional study was conducted to investigate the immune memory responses of H7N9 patients who contracted the disease and survived during the 2013–2016 epidemics in China. Sustainability of antibodies and T-cell memory to H7N9 virus were examined. Healthy individuals receiving routine medical examinations in a physical examination centre were recruited as control. Results: A total of 75 survivors were enrolled and classified into four groups based on the time elapsed from illness onset to specimen collection: 3 months ( n  = 14), 14 months ( n  = 14), 26 months ( n  = 28) and 36 months ( n  = 19). Approximately 36 months after infection, the geometric mean titres of virus-specific antibodies were significantly lower than titres in patients 3 months after infection, but 16 of 19 (84.2%) survivors in the 36-month interval had microneutralization (MN) titres ≥40. Despite the overall declining trend, the percentages of virus-specific cytokine-secreting memory CD4 + and CD8 + T cells remained higher in survivors at nearly all time-points in comparison with control individuals. Linear regression analysis showed that severe disease (mean titre ratio 2.77, 95% CI 1.17–6.49) was associated with higher haemagglutination inhibition (HI) titre and female sex for both HI (1.92, 1.02–3.57) and MN (3.33, 1.26–9.09) antibody, whereas female sex (mean percentage ratio 1.69, 95% CI 1.08–2.63), underlying medical conditions (1.94, 95% CI 1.09–3.46) and lack of antiviral therapy (2.08, 95% CI 1.04–4.17) were predictors for higher T-cell responses. Conclusions: Survivors of H7N9 virus infection produced long-term antibodies and memory T-cell responses. Our findings warrant further serological investigation in general and high-risk populations and have important implications for vaccine design and development.